Recurrent reactive non-sexually related acute genital ulcers: a risk factor for Behcet’s disease? - Brambilla, Ilaria; Moiraghi, Alice; Guarracino, Carmen; Pistone, Carmelo; Tondina, Enrico; Riccipetitoni, Giovanna; Raffaele, Alessandro; Cavaiuolo, Silvia; Bertozzi, Mirko; Brazzelli, Valeria (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Lipschutz ulcers (LU) are idiopathic genital lesions characterized by the sudden appearance of painful, usually symmetric vulvar ulcers, typically occurring in sexually inactive adolescents. LU is a diagnosis of exclusion. As these lesions heal spontaneously, in the absence of tissue scarring, the therapy is mainly symptomatic and focuses on pain relief. Recurrence of LU associated with oral ulcers describes the clinical picture of complex aphthosis, which belongs to Behçet’s disease (BD) pathological spectrum. Our work aims to analyze the correct diagnostic approach to recurrent aphthous, focusing on the importance of a multidisciplinary assessment and immunogenetic investigation to identify the subjects at risk of progression towards BD. Methods: We present the case of a 12-year-old non sexually active Italian girl who was diagnosed with LU. After 15 months, she presented recurrent reactive non sexually related acute genital ulcer associated with a history of oral aphthous. According to clinical features and anamnesis, complex aphthosis was diagnosed. For diagnostic purposes, she underwent an immunogenetic analysis that showed HLA-B51 positivity. Results: In the absence of clinical and laboratory criteria to define the risk of progression of complex aphtosis towards BD, we think that besides a strict follow-up, in pediatric patients with a suggestive clinical history, it is crucial to adopt a multidisciplinary approach, comprehensive of HLA investigation, in order to guarantee an early diagnosis and a prompt therapeutic intervention. Conclusions: In children and adolescents with genital ulcers, it is essential to consider all the possible differential diagnoses to undertake a timely and correct course of treatment.